Community-based monitoring for environmental sustainability: A review of characteristics and the synthesis of criteria. (1st July 2021) - Muhamad Khair, Nur Khairlida; Lee, Khai Ern; Mokhtar, Mazlin
Abstract: Community-based monitoring is increasingly recognised as one solution to sustainable environmental management. However, the development of community-based monitoring has led to confusion or misconceptions regarding other similar initiatives. Through a review of the characteristics and synthesising criteria of effective community-based monitoring, this article addresses how to distinguish community-based monitoring from other forms of community engagement research. A review of relevant community-based monitoring literature identifies the characteristics of and knowledge gaps in procedures and governance structures. Additionally, evidence of common benefits, challenges and lessons learned for successful community-based monitoring are deliberated. As an outcome of the review, the article synthesises a set of community-based monitoring criteria as follows: (1) efficacy of initiatives, (2) technicality aspects, (3) feedback mechanisms and (4) sustainability. These synthesised criteria will be instrumental in designing customised community-based monitoring initiatives for environmental sustainability. Highlights: CBM is increasingly recognised as solution to sustainable environmental management. The design of CBM should consider community motivation and capacity. CBM criteria: efficacy, technicality, feedback mechanisms and sustainability. Effective CBM should couple with sound implementation mechanisms.